(untitled) (Transport systems and technologies, 2021)
The article examines the influence of freight transportation technology on special conditions according to the schedule of route trains on the quantitative and qualitative indicators of the operational work of the railway system of Ukraine. The calculations of the components of the freight car turnover are carried out. It was found that the strategy of routing, transportation by RRMP and coordination of loading and unloading terms significantly reduced the downtime of the car under freight operations. The analysis of indicators shows that the implemented technology of cargo transportation according to the RRMP allowed in 2019 to achieve a reduction within the busy flight of the number of technical stations from five stations in 2018 to 4.7 in 2019. The comparative analysis of technical and district speed is carried out and the speed coefficient is calculated. According to the analysis of the change in the speed factor, it can be stated that the ratio of precinct to technical speed remained unchanged in 2019 compared to 2018, which may indicate the lack of impact of transportation technology on dispatching, which was essentially unchanged for two years. Simulation according to the analytical approach of change of turnover of a freight car at increase in a share of transportations of freights under contracts on special conditions is executed. Calculations prove that with the increase of the share of cars of the working fleet, organized in the transportation of goods by RRMP in the element of car turnover - simple car at technical stations, can significantly reduce the overall turnover of the car. The influence of the technology of transportation according to the schedule on the reduction of the most significant element in the turnover of the car - the downtime of the car under freight operations.